NATIONAL AND FOREIGN EXPERIENCE: IMPROVING THE LEGAL FRAMEWORK FOR ENSURING PROSECUTORIAL SUPERVISION OVER THE IMPLEMENTATION OF LAWS ON THE LEGAL PROTECTION OF MILITARY SERVICEMEN OF THE ARMED FORCES (ON THE BASIS OF THE EXPERIENCE OF LITHUANIA, LATVIA A (World Bulletin of Management and Law, 2026)
The article analyzes the role and significance of prosecutorial supervision in ensuring the legal protection of military servicemen of the Armed Forces, examining the functions of prosecutorial bodies in upholding the rule of law. It also provides a comparative study of the specific reforms in the military justice systems of the Baltic states (Lithuania, Latvia, and Estonia). In addition, the study presents scientifically grounded proposals aimed at strengthening the socio-legal status of military servicemen, improving mechanisms for preventing violations of their rights, and implementing positive aspects of foreign experience into national legislation in this field.
Keywords: Armed Forces; law; military serviceman